2021
DOI: 10.3390/ijerph182211958
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Stress among Saudi Arabian Nursing Students: A Cross-Sectional Study

Abstract: Introduction: Nursing students experience higher levels of stress than those in other health-related disciplines; however, there are limited data exploring stress among these students in a Saudi context. Aim: This study examines sources of stress among nursing students at an academic institution in Jeddah, Saudi Arabia, using a descriptive quantitative cross-sectional research design. Methods: Data were collected from a convenience sample of 500 undergraduate nursing students, with a response rate of 71.8%, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…In the evaluation eligibility stage, out of 225 remaining articles, 210 ineligible articles were removed following the examination of their full text, and similarly according to the inclusion and exclusion criteria. In the quality evaluation stage, by reading the full text of the article and based on the score obtained from AHRQ checklist, 15 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were entered into the final analysis (Fig. 2).…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the evaluation eligibility stage, out of 225 remaining articles, 210 ineligible articles were removed following the examination of their full text, and similarly according to the inclusion and exclusion criteria. In the quality evaluation stage, by reading the full text of the article and based on the score obtained from AHRQ checklist, 15 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were entered into the final analysis (Fig. 2).…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Fifteen studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included, including 9202 patients. The results of the meta-analysis showed that the average score for stress among nursing students was 3.70 (95% confidence interval [CI]: [3.33, 4.06]).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Sources of stress in nursing students mainly arise from clinical learning, academic study, and issues in their social lives [ 6 , 7 , 8 ]. The clinical learning-related stressors include a lack of knowledge and skills to perform the patient care, and heavy workloads [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, Jones, Hansen, Kaddoura, Schwab-McCoy and Tocchini [56] emphasized that nursing students experience considerably elevated levels of stress. In Saudi Arabia, nursing students had the highest levels of stress [57]. In addition, a significant prevalence of stress among university students has been found in numerous research [58,59].…”
Section: Discussionmentioning
confidence: 97%